PENGARUH PERSEPSI PENGUSAHA KECIL ATAS INFORMASI AKUNTANSI KEUANGAN TERHADAP KEBERHASILAN PERUSAHAAN (Survei Pada Usaha-Usaha Kecil Di Kota Medan) - Zulia Hanum (Jurnal Riset AKuntansi dan Bisnis, 2013)
The purpose of this study was to determine the influence of positivecorrelation between learning, motivation, and personality on perceptions of small business owners on financial accounting information and whether there is a positive influence on the perception of businessmen on accounting information to the company's success in the Small and Medium Enterprises (SMEs) in Medan. The research was conducted on SMEs in Medan by using survey methods.The results showed that: (1) Learning, Motivation and Personality jointlyhave a significant influence Perception Of Accounting For information on SMEs in Medan. (2) The learning process does not have an influence on the perception of small businesses on accounting information. This suggests that a good learning process has not been able to ensure the growing perception of small businesses on accounting information on SMEs in Medan. (3) Motivation has an influence on the perception of small businesses on accounting information. This suggests that small business owners high motivation to guarantee small business owners increase the perception of accounting information on SMEs in Medan. (4) Personality does not have an influence on the perception of small businesses on accounting information. This suggests that a good personality not been able to guarantee the improvement of the perception of small business accounting information on SMEs in Medan. (5) The perception of small businesses on accounting information had no effect on the success of the business. This suggests that the perception of small businesses on accounting information either not able to guarantee the improvement of business success in SMEs in Medan